Economic Analysis of Moonlighting in Higher Education Institutes of Khyber Pakhtunkhwa - Jehan, Noor; Khan, Himayatullah (The Journal of Humanities & Social Sciences, 2023)
The main objective of this study is to investigate the determinants of moonlighting in public sector universities of KP. A multi-staged sampling was used for data collection. In the first stage, the population was stratified into rural, semi-urban and urban universities and 9 universities were purposively selected. In the second stage, in each selected university teaching faculty was further stratified into Professors, Associate Professors, Assistant Professors, Lecturers and Teaching Assistants. In the third stage, a sample of 656 faculty members was selected using simple random sampling and proportional allocation method. Binary Logistic regression model was used as the dependent variable was of dichotomous nature (moonlighting vs. no moonlighting). Wage rate of second job, accumulative wage of more than one second jobs, employment status and cadre, hours of work at second job, location and marital status were found significant in determining moonlighting. Based on its findings, the study recommended that moonlighting may be encouraged which may not only enhance moonlighter’s income but also their efficiency. The study also recommended that studies on moonlighting in other sectors may also be conducted which could help policy planners, researchers and other stack holders.